Identification of a protein component of a mammalian tRNA(Sec) complex implicated in the decoding of UGA as selenocysteine. - Ding, F (1999)
This report describes a novel RNA-binding protein, SECp43, that associates specifically with mammalian selenocysteine tRNA (tRNA(Sec)). SECp43, identified from a degenerate PCR screen, is a highly conserved protein with two ribonucleoprotein-binding domains and a polar/acidic carboxy terminus. The protein and corresponding mRNA are generally expressed in rat tissues and mammalian cell lines. To gain insight into the biological role of SECp43, affinity-purified antibody was employed to identify its molecular partners. Surprisingly, the application of native HeLa cell extracts to a SECp43 antibody column results in the purification of a 90-nt RNA species identified by direct sequencing and Northern blot analysis as tRNA(Sec). The purification of tRNA(Sec) by the antibody column is striking, based on the low abundance of this tRNA species. Using recombinant SECp43 as a probe for interacting protein partners, we also identify a 48-kDa interacting protein, which is a possible component of the mammalian selenocysteine insertion (SECIS) pathway. To our knowledge, SECp43 is the first cloned protein demonstrated to associate specifically with eukaryotic tRNA(Sec).